Assessment of Pelvic Floor Disorders due to the Gestational Diabetes Mellitus Using Three-Dimensional Ultrasonography: A Narrative Review - Sartorão Filho, Carlos Izaias [UNESP] (2022)
Gestational diabetes mellitus (GDM)is an entity with evolving conceptual nuances that deserve full consideration. Gestational diabetes leads to complications and adverse effects on the mother's and infants' health during and after pregnancy. Women also have a higher prevalence of urinary incontinence (UI) related to the hyperglycemic status during pregnancy. However, the exact pathophysiological mechanism is still uncertain. We conducted a narrative review discussing the impact of GDM on the women's pelvic floor and performed image assessment using three-dimensional ultrasonography to evaluate and predict future UI.